Properties and occurrence of clay resources for use as supplementary cementitious materials: a paper of RILEM TC 282-CCL - Alujas Diaz, Adrian; Almenares Reyes, Roger S.; Hanein, Theodore; Irassar, Edgardo F.; Juenger, Maria; Kanavaris, Fragkoulis; Maier, Matthias; Marsh, Alastair T.; Sui, Tongbo; Thienel, Karl-Christian; Valentini, Luca; Wang, Bin; et al. (Materials and structures, 2022)
The use of clays as resource of supplementary cementitious materials (SCMs) for a new generation of low-carbon cements and concretes is currently the subject of intense research efforts. To this purpose, a large number of clay resources have been explored, characterized and evaluated. This paper introduces the basic knowledge and concepts on clay occurrence and clay mineralogy, before presenting up-to-date knowledge on properties and occurrence of clay resources suitable for use as SCMs. Occurrence, distribution and chemical and mineralogical selection criteria are discussed for kaolinitic clays, which often show superior reactivity and performance. 2:1 clay mineral resources have received somewhat less attention as SCM resources, however recent developments indicate significant potential for calcined impure common clays, and are reviewed. An overview of ubiquitous clay mineral-bearing waste materials also identifies important opportunities for alternative clay sourcing in mining or extraction residues, and dredged or excavated sediments.